Chemically imidized semi-alicyclic polyimides: the effect of catalyst type and imidization temperature - Šimonová, Zuzana Frances; Machotová, Jana; Zelenka, Jiri; Vlček, Miroslav; Šimon, Pavel (Springer, 2023)
Polyimides are a group of polymers with excellent thermal and mechanical properties. However, generally, they exhibit brown coloration due to charge transfer interactions between diamine donor and dianhydride acceptor moieties. In this study, semi-alicyclic polyimides derived from cyclohexane tetracarboxylic dianhydride and 4,4 '-oxydianiline were prepared using a two-step method, where the imidization step proceeded via a chemical route. The effects of the catalyst type (quinoline, triethylamine, and 1,4-diazabicyclo(2.2.2)octane (DABCO)) and reaction temperature (120, 140, and 160 C-degrees) on the imidization process were evaluated using infrared spectroscopy and nuclear magnetic resonance spectroscopy. The prepared polyimides' thermal, mechanical, and optical properties were compared with those synthesized via standard thermal imidization. Polyimide films possessing favorable mechanical properties, thermal stability, and good optical transparency were prepared via a simple preparation route based on chemical imidization using the triethylamine catalyst at the reaction temperature of 160 C-degrees, which was shown to be a promising way for the PI preparation on an industrial scale.
Chemicky imidizované transparentní semi-alicyklické polyimidy: Vliv typu katalyzátoru a teploty imidace
Keywords: colorless polyimides; soluble polyimides; polyalicyclic structure; thermal imidization; curing accelerators; aromatic polyimides; polyamic acids; films; dianhydride; polyimidy; chemická imidizace; triethylamin